Urgensi Modifikasi Habituasi pada Masa Pandemi Covid 19 bagi Interaksi Sosial Generasi Milenial - Wening Purbatin Palupi Soenjoto (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
The Covid 19 pandemic has not yet ended and so far the impact that is being felt is more on psychological fatigue. Changes in behavior at the start of the pandemic caused psychological shock and global anxiety. Physical and psychological unpreparedness to face the covid 19 pandemic has resulted in the emergence of forced new behaviors and greatly changed habituation. The pattern of changing habituation suddenly and being forced is not easy. Even with the imposition of sanctions and the emergence of new normal life regulations, it still requires a long process. And does not guarantee compliance evenly in various regions. For the millennial generation who believe in the existence of the Covid 19 virus with real evidence, it has a psychological impact and forces them to change their habituation according to the health protocols that are implemented so that their health is maintained. to comply with health protocols simply because of fear of being penalized. Research Results: The form of social reality during the Covid 19 pandemic was the result of a series of interactions between social actors in an environment. social reality as something that is a label and concept in interpreting the covid 19 pandemic. Research Purpose: Used to build reality or something that is not real. How is the millennial generation able to change habituation which is considered as a way to understand an event. Research Method: This research uses qualitative methods with an interpretive approach. This interpretive nature assumes that individuals see and build social reality actively and consciously, so that each individual must have a different meaning in an event. Conclusion: social interaction in the millennial generation during this pandemic is a reciprocal relationship that influences, changes, or improves behavior that takes place between individuals and individuals, individuals and groups, or groups and groups so that changes in behavior are formed or mutually form compulsions but with consistency it becomes a habituation. So the meaning of urgency in habituation modification is something that is considered necessary to be applied as a form of protecting oneself and others.